Epilepsy-induced electrocardiographic alterations following cardiac ischemia and reperfusion in rats - Tavares,J.G.P. (2015)
The present study evaluated electrocardiographic alterations in rats with epilepsy submitted to an acute myocardial infarction (AMI) model induced by cardiac ischemia and reperfusion. Rats were randomly divided into two groups: control (n=12) and epilepsy (n=14). It was found that rats with epilepsy presented a significant reduction in atrioventricular block incidence following the ischemia and reperfusion procedure. In addition, significant alterations were observed in electrocardiogram intervals during the stabilization, ischemia, and reperfusion periods of rats with epilepsy compared to control rats. It was noted that rats with epilepsy presented a significant increase in the QRS interval during the stabilization period in relation to control rats (P<0.01). During the ischemia period, there was an increase in the QRS interval (P<0.05) and a reduction in the P wave and QT intervals (P<0.05 for both) in rats with epilepsy compared to control rats. During the reperfusion period, a significant reduction in the QT interval (P<0.01) was verified in the epilepsy group in relation to the control group. Our results indicate that rats submitted to an epilepsy model induced by pilocarpine presented electrical conductivity alterations of cardiac tissue, mainly during an AMI episode.